Gender, affect and intertemporal consistency: an experimental approach - Kendra N. McLeish; Robert J. Oxoby (Institute for the Study of Labor (IZA), 2007)
We conduct experiments in which participants made multiple intertemporal decisions throughout a seven week period. In addition to exploring dynamic consistency and the stability of single period discount rates, our experiments introduce a manipulation to identify the role of positive and negative mood/affect in intertemporal choice. Our results demonstrate that, while individuals' single period discount rates are stable over time, there is evidence of dynamic inconsistency. While we find no differences in the discount rates of men and women, we find gender differences in the character of hyperbolic discounting in which women display greater patience in their present bias. We also identify a gender-mood interaction: Negative mood in women yields increased impulsiveness while inducing positive affect in women or affect (positive or negative) in men yields little change
urn:nbn:de:101:1-20080415129
Keywords: 330; Entscheidung; Zeitpräferenz; Emotion; Geschlecht; Test; Kanada